Rear Electrode Materials for Perovskite Solar Cells - Chen, Rui; Zhang, Wenjun; Guan, Xinyu; Raza, Hasan; Zhang, Shasha; Zhang, Yiqiang; Troshin, Pavel A.; Kuklin, Sergei A.; Liu, Zonghao; Chen, Wei (Advanced functional materials, 2022)
Perovskite solar cells (PSCs) represent a promising next‐generation photovoltaic technology considering their high efficiency and low cost. At the current stage, resolving the stability bottleneck is extremely urgent to realize PSCs’ commercialization since the efficiencies of these cells are improved to a level comparable to that of crystalline silicon solar cells. Similar to other functional layers, a proper choice of the rear electrode atop the perovskite layer is equally important for achieving the device's long‐term stability. This topic has not been comprehensively reviewed before. Here, recent progress in the development of rear electrodes based on metals, carbon‐based materials, transparent conductive oxides, and conductive polymers is summarized, especially focusing on their different impacts on the device's long‐term stability and associated degradation mechanisms. In the context of practical applications, the impacts of rear electrode materials on the device's overall efficiency and cost‐effectiveness are also discussed. Here, recent progress in the development of perovskite solar cells’ rear electrodes based on metals, carbon‐based materials, transparent conductive oxides, and conductive polymers is summarized, especially focusing on their different impacts on the device's long‐term stability and embedded degradation mechanisms. For practical applications, the impacts of rear electrodes on the device's overall efficiency and cost‐effectiveness are also discussed.